Rethinking Sustainability in the Digital Age: FinTech, Economic Growth, and the Load Capacity Curve in the United States - Pabel, Md Amran Hossen; Tasnuva, Tahia; Farukh, Md Omar; Tithi, Shamina Israt; Mo, Kuan (Optimality, 2026)
This study explores the role of Financial Technology (FinTech) and the digital economy in shaping ecological sustainability in the United States over the period 1990–2021 within the framework of the Load Capacity Curve (LCC) hypothesis. Moving beyond conventional indicators, environmental sustainability is proxied by the Load Capacity Factor (LCF), which captures the balance between ecological demand and regenerative capacity. The analysis employs the Autoregressive Distributed Lag (ARDL) approach to estimate both long-run relationships and short-run dynamics, while Fully Modified Ordinary Least Squares, Dynamic Ordinary Least Squares, and Canonical Cointegrating Regression are used to ensure robustness. The findings reveal a nonlinear association between economic growth and ecological sustainability, confirming the validity of the LCC hypothesis, where environmental conditions initially deteriorate but improve at higher income levels. FinTech and digitalization are found to exert a significant positive influence on sustainability, suggesting that digital financial innovations enhance resource efficiency and facilitate environmentally responsible investments. In contrast, Urbanization (URBA) contributes negatively, reflecting the environmental pressures associated with rapid population concentration and infrastructure expansion. Overall, the results highlight the critical importance of aligning digital transformation with sustainability-oriented policies to achieve long-term ecological balance and resilience.